BELIAN NAMANG SEBAGAI RITUAL PENCARIAN ROH ORANG MENINGGAL DESA KEDANG IPIL, KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR - Nur Asmarita Viana (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
This research aims to find out about the naming ritual as a ritual to search for the spirits of the dead in Kedang Ipil Village. The method used in this research is qualitative. Data collection was carried out by means of interviews, observation and documentation. The results of this research show that the ritual of buying namang inherited by the people of Kedang Ipil Village is still maintained and maintained to this day. This ritual is carried out to find the spirit of a person who has died for 15 days.